Structure of a computer (New York : [Distributed by] Harper & Row, 1976)
Introduces computing and the ways in which a computer can be used as an aid to problem solving.
Converted into VHS 1/2 in. and DVD.
Bahan rosak (Lupus)
Keywords: Computers; Electronic data processing